2017
DOI: 10.1177/1745691616662473
|View full text |Cite
|
Sign up to set email alerts
|

A Growing Disconnection From Nature Is Evident in Cultural Products

Abstract: Human connection with nature is widely believed to be in decline even though empirical evidence is scarce on the magnitude and historical pattern of the change. Studying works of popular culture in English throughout the 20th century and later, we have documented a cultural shift away from nature that begins in the 1950s. Since then, references to nature have been decreasing steadily in fiction books, song lyrics, and film storylines, whereas references to the human-made environment have not. The observed temp… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
101
0
4

Year Published

2018
2018
2022
2022

Publication Types

Select...
6
2
1

Relationship

0
9

Authors

Journals

citations
Cited by 142 publications
(106 citation statements)
references
References 47 publications
1
101
0
4
Order By: Relevance
“…The extant literature suggested that there were inadequate studies conducted to understand the relationship between smartphone usage and environmental behaviors, which this study sought to fill the gap by investigating personal norms, social norms, and perceived behavioral control to determine their specific path and level of influence on pro-environmental behaviors. The overall results indicated that moderate smartphone usage children had shown a greater level of proenvironmental behaviors than those children who were excessive smartphone users, and this finding was supported by previous studies [8,9]. The results also revealed support and accepted six (i.e.…”
Section: Discussionsupporting
confidence: 83%
See 1 more Smart Citation
“…The extant literature suggested that there were inadequate studies conducted to understand the relationship between smartphone usage and environmental behaviors, which this study sought to fill the gap by investigating personal norms, social norms, and perceived behavioral control to determine their specific path and level of influence on pro-environmental behaviors. The overall results indicated that moderate smartphone usage children had shown a greater level of proenvironmental behaviors than those children who were excessive smartphone users, and this finding was supported by previous studies [8,9]. The results also revealed support and accepted six (i.e.…”
Section: Discussionsupporting
confidence: 83%
“…Particularly, the widespread use of smartphones is regarded as a factor influencing pro-environmental behavior, leading to disconnect people from the natural environment which has become substantial worldwide psychological and behavioral issues [5,6]. While it remains controversial whether smartphone usage cause disconnectedness between people and natural environment [7,8], studies have found that adults who spent extended amount of time on smartphone in a day are more likely to exhibit a stronger negative pro-environmental behavior [8,9]. Such extensive smartphone usage behavior is not only limited to adults, but also evident in children who are increasingly smartphone users nowadays.…”
mentioning
confidence: 99%
“…La biodiversidad es un concepto que se cree ampliamente conocido, o por lo menos ampliamente comentado en la sociedad y la escuela, así como una necesidad de conservación ambiental. Y, sin embargo, algo en estos procesos no acaba de funcionar en los procesos de enseñanza-aprendizaje implementados, cuando nos encontramos cada vez más alejados de la naturaleza (Kesebir & Kesebir, 2017;Prévot-Julliard, Julliard & Clayton, 2015;Pyle, 2003), relación que se considera imprescindible para poder conseguir un desarrollo óptimo en la infancia (Corraliza & Collado, 2011;Torres-Porras et al, 2017).…”
Section: Investigación De Fondounclassified
“…Other work has explored shifts in societies think about and engage with the natural world. In their analysis of references to nature in cultural products, Kesebir and Kesebir (2017) report a decline in nature-related language (i.e. references to birds, trees, flowers, seasons, etc) in American and British fiction, popular song lyrics from Anglophone countries, and storylines from Anglophone films from the mid-twentieth century onwards.…”
Section: Relationship With the Natural Worldmentioning
confidence: 99%